Pengaruh Harga, Lokasi, Dan Brand Image Terhadap Loyalitas Pelanggan Tomoro Coffee Di Kota Malang. - Desty Nur Cahyani; Achmad Agus Priyono; Tri Sugiarti Ramadhan (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to determine and analyze the effect of price, location, and brand image on customer loyalty at Tomoro Coffee in Malang City. This research uses an explanatory research method with a quantitative approach. The data were collected through questionnaires distributed to 80 respondents, consisting of students of Universitas Islam Malang class of 2021 who have made at least one purchase at Tomoro Coffee Dinoyo branch. The sampling technique used in this study is purposive sampling. The data analysis method applied is multiple linear regression to examine the relationship between variables. The results of this study indicate that price, location, and brand image simultaneously have a significant effect on customer loyalty. Partially, each variable, namely price, location, and brand image, also has a positive and significant effect on customer loyalty. Price reflects the value received by customers, location provides ease of access and convenience, while brand image builds positive perceptions in the minds of consumers. These findings suggest that improving pricing strategies, selecting strategic locations, and strengthening brand image are essential factors in increasing customer loyalty. Therefore, companies are expected to optimize these variables to maintain and enhance long-term customer relationships. Keywords: Price, Location, Brand Image, Customer Loyalty